Rancang Bangun Pengering Ikan Asin Higienis Menggunakan Fotovoltaik - Akhmad Fadli Ibrahim; Yuvita Satriani Djuli (Program Pendidikan Vokasi Teknik Mesin, 2023)
The traditional fish drying process carried out by fishermen by placing it under direct sunlight still causes several problems, such as rainy weather conditions and hygiene of the dried fish. The purpose of this research is to overcome the problems in the traditional fish drying process, by using a closed container photovoltaic dryer with the help of a heating element. The results obtained by using the dryer can save drying time which initially takes 3-5 days to only 12 hours. The drying process using this tool can work even if the weather conditions are rainy or at night. The total time required during the fish drying process reached 12 hours with light intensity rain weather conditions. The results obtained are much better than the traditional drying time which takes 3-5 days on average for the drying process. In addition to saving drying time, the salted fish is also visually more hygienic than the traditional drying process, because it is in a dryer that is protected from dirt and virus-carrying animals. The resulting product needs further testing from a health perspective, although it works well mechanically.